In Vitro and In Vivo Activities of NS-718, a New Lipid Nanosphere Incorporating Amphotericin B, against Aspergillus fumigatus - Otsubo, Takakazu (American Society for Microbiology, 1999)
We evaluated the in vitro and in vivo potencies of a new lipid nanosphere that incorporates amphotericin B (AmB), NS-718, against Aspergillus fumigatus. The in vitro activity of NS-718 (the MIC at which 90% of strains are inhibited [MIC(90)], 0.25 μg/ml) against 18 isolates of A. fumigatus was similar to that of deoxycholate AmB (D-AmB; Fungizone; MIC(90), 0.25 μg/ml), but NS-718 was more potent than liposomal AmB (L-AmB; AmBisome; MIC(90), 1.0 μg/ml). The in vivo efficacy of NS-718 in a rat model of invasive pulmonary aspergillosis was compared with those of D-AmB and L-AmB. A low dose (1 mg/kg of body weight) of L-AmB was ineffective (survival rate, 0%), although equivalent doses of D-AmB and NS-718 were more effective (survival rate, 17%). However, a higher dose of NS-718 (3 mg/kg) was more effective (survival rate, 100%) than equivalent doses of D-AmB and L-AmB (survival rate, 0%). To explain these differences, pharmacokinetic studies showed higher concentrations of AmB in the plasma of rats treated with NS-718 than in the plasma of those treated with D-AmB. Our results suggest that NS-718, a new preparation of AmB, is a promising antifungal agent with activity against pulmonary aspergillosis.